Explanation Exploration: Exploring Emergent Behavior - Gore, Ross; Reynolds Jr, Paul F.; Tang, Lingjia; Brogan, David C. (21st International Workshop on Principles of Advanced and Distributed Simulation (PADS 2007): San Diego, California - 12-15 June 2007, 2007)
Understanding emergent behavior(s) exhibited in simulations poses an interesting challenge. Emergence can represent a valid behavior arising from seemingly unrelated phenomena, or it can reflect an error in a model or its implementation. We propose a new method for gathering insight into emergent behavior in simulations using the model adaptation technique, COERCE. COERCE allows a user to efficiently adapt a model to meet new requirements and can be employed to explore emergent behavior exhibited in a simulation. A subject matter expert (SME) can coerce a simulation to gather insight into characteristics of the emergent behavior as the simulated phenomenon is driven toward conditions of interest.